DIREÇÃO E VELOCIDADE DO VENTO EM UMA FLORESTA DE TRANSIÇÃO AMAZÔNIA-CERRADO NO NORTE DE MATO GROSSO, BRASIL - Stéfano Teixeira Silva; Elis Dener Lima Alves (Boletim Goiano de Geografia)
The objective of the work was to determine the predominant wind direction and speed in a region of rain Amazon-Savanna transition forest, located approximately 50 km from the city of Sinop, in northern Mato Grosso, Brazil.The daily directions wind and speeds were collected by a three-dimensional sonic anemometer-thermometer,installed in a tower at a height of 12 m above the forest canopy. The predominant wind direction was characterizedby a frequency analysis of the daily observations, for each one of the stations and months of the year. In mostof the year there is predominance of south-southeast and south-southwest winds. It was observed that therewas no direct relation between the time and the wind direction, and the same showing a seasonal variation,there is a direct relation just with the wind speed. In the dry season showed that the predominant winddirection was south-southwest. Already in dry-wet and wet seasons the winds flowed in all directions.